Organising Traditional Knowledge for Inclusive Development: Role of Libraries (Bangladesh Journal of Library and Information Science, 2012)
In this paper we discuss traditional knowledge, its importance especially in inclusive development and knowledge management activities taken up in West Bengal. We also focus on the role of libraries especially public libraries in preserving and propagating this cultural heritage and traditional knowledge. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.5-11DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12914